The Effect of Agility Training On Football Dribbling Skills of Students At Tanjungsiang Elementary School (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of agility training on improving football dribbling skills in Tanjungsiang State Elementary School students. Dribbling is an important basic technique in the game of soccer, which requires ball handling, speed, and body balance. Agility exercises were chosen because they can improve motor skills and movement control when dribbling. The research method used was a one-group pretest-posttest using dribbling skill test instruments before and after the administration of agility training. The sample of this study was 30 students who met certain criteria. The results of the analysis showed a significant improvement in students' dribbling skills after participating in agility exercises, evidenced by a p-value of < 0.05 and an increase in average scores from pretest to posttest. These results state that agility training has a positive and significant effect on improving the soccer dribbling skills of elementary school students. Therefore, agility training can be used as an effective strategy in learning football technical skills at the elementary school level.